On some computer tomography mathematical problems - Čiegis, Raimondas; Krylovas, Aleksandras; Meilūnas, Mečislavas (Lietuvos matematikos rinkinys, 2003)
In this paper we investigate a new algorithm for determination of a human brain ischemic stroke region on CT images. The algorithm uses the initial CT information, i.e., values of linear integrals obtained in different directions. This gives a possibility to get a preliminary information about the stroke region faster then using the inverse transformations for obtaining the full CT picture of the brain.